THE GENUS CYNOMETRA (LEGUMINOSAE) IN CEYLON - kostermans, a. j. g. h. (Research Center for Biology, 1982)
In Ceylon 2 species of Cynometra occur, the wide spread C. iripa of the mangroves, which was enumerated as Cynometra ramiflora var. heterophylla by Thwaites and wrongly included in C. ramiflora by Knaap-van Meeuwen and the new species C. zeylanica Kosterm., formerly thought to be the Malesian C. ramiflora. The latter, as defined by Prain and based on a Rumphian plate, does not occur in Ceylon. Cultivated is the Malesian C. cauliflora with a white- and a pink-flowered forms.